STUDENTS’ DEMOTIVATION FACTORS IN LEARNING ENGLISH at MTs NEGERI 1 BAUBAU - La Mido; Asmita Asmita (English Education Journal, 2023)
This study aims to reveal the internal factors that cause student demotivation in learning English and to reveal the external factors that cause student demotivation in learning English. Data collection in this study was carried out using research instruments in the form of observation, interviews, and document study to find out the internal factors that cause students demotivation in learning English and the external factors that cause students demotivation in learning English, interviews were conducted to ensure the data obtained could be valid. The data obtained were analyzed with a descriptive qualitative approach and analyzed through three stages, namely data reduction, data display, and verification. The researchers saw that students were less enthusiastic and eager to learn English, this could be due to their low interest in learning English, besides that the researchers also saw that the teacher's teaching methods were still less creative, lack of appreciation to students and still lack of supporting facilities for learning English. Based on the results of interviews conducted with ten eighth-fourth grade students and teachers of English subjects researchers can conclude that there are several internal factors that cause students not to be motivated to learn English, namely their low interest in learning English, students also feel difficulty in learning English and they often feel bored when learning English and external factors that cause students to be unmotivated to learn English is the attitude of the teacher when teaching, lack of interaction between teachers and students in the school environment, students also feel that the teacher's teaching style is still less attractive, students' difficulty in doing assignments due to lack of English vocabulary, the influence of classmates who mostly do not like English, the lack of availability of library books and the low interest in reading students, and the last is the lack of support or attention from the family to the student's learning process